Technofunctional characterisation of a protein concentrate from the red seaweed, Palmaria palmata - Anthony Temitope Idowu; Miryam Amigo-Benavent; Richard.J. FitzGerald (Applied Food Research)
The technofunctional properties of a Palmaria palmata protein concentrate (PPPC, 47 % (w/w) protein) generated at semi-pilot scale were assessed. The overall solubility, nitrogen solubility index (NSI), colour, electrophoretic profile, water and oil binding capacity (WBC and OBC), foam capacity and stability, emulsifying properties, particle size distribution, heat stability and apparent viscosity at pH 3.0–9.0 of the PPPC was characterised. Whey protein concentrate (WPC, 56 % (w/w) protein) was used as a reference protein ingredient. The highest overall solubility was obtained at pH 9.0 for both PPPC (64.06 ± 4.80 %) and for WPC (89.34 ± 4.66 %). The NSI, WBC, foam and emulsifying, particle size distribution, heat stability and apparent viscosity properties for PPPC and WPC were dependent of the reconstitution pH. The PPPC had a significantly (p < 0.05) higher OBC (3.70 ± 0.04 g of oil/g of protein) than WPC (1.73 ± 0.03 g of oil/g of protein). These findings indicated that PPPC has potential as an alternative protein ingredient in products where WBC and OBC properties are required.